COVID-19 pandemisi sürecinde meme radyolojisi - Durur Subaşı, Irmak (Dr. Abdurrahman Yurtaslan Ankara Oncology Training and Research Hospital, 2020)
Meme kanseri taramasının en önemli amacı, kanserin erken evrede yakalanarak meme kanserine bağlı ölümlerin azaltılmasıdır. COVID-19 salgını, hastaların ve sağlık çalışanlarının sağlık durumu ile ilgili acil bir sorun olarak kısa bir süre önce dünya gündemini ve genel kaygıları değiştirmiştir. Hala meme taramanın amacı mortaliteyi azaltmaktır; ancak bunun COVID-19 (SARS-COV-2) kaynaklı ölümlere neden olmaması için ayrıntılı rehberler oluşturulmalıdır.

The most important goal of breast cancer screening is to detect cancer at an early stage and reduce deaths due to breast cancer. The COVID-19 pandemic has recently changed the world agenda and general concerns as an urgent issue regarding the health status of patients and healthcare workers. Still, the goal of breast screening is to reduce mortality; However, detailed guidelines should be created so that this does not cause deaths from COVID-19 (SARS-COV-2).
Breast radiology practices during the Covid-19 pandemic
Keywords: Biyopsi; Mamografi; Meme Ultrasonografisi; SARS-COV-2; Biopsy; Breast Ultrasonography; Mammography; SARS-COV-2